1986
DOI: 10.1002/ajp.1350110309
|View full text |Cite
|
Sign up to set email alerts
|

Breeding performance of captive‐born cotton‐top tamarin (Saguinus oedipus) females: Proposed explanations for colony differences

Abstract: Successful breeding by captive‐born Saguinus oedipus females has now been reported from several colonies, but a marked parity effect (ie, differences in infant survival with the number of litters produced) is usually observed; survival of infants of primiparous females is extremely low but increases with subsequent litters. This parity effect was not observed in the captive‐born breeding females in the Oak Ridge Associated Universities colony, with survival of offspring of primiparous females at 58.6%. Two exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…This effect is likely to be due to two interacting factors: a decrease in the average litter size born (in contrast with Tardif et al [1986], who found an increase), and an increase in the number of infants surviving from each litter. The delayed improvement occurred despite the fact that all breeding females had had considerable experience with infant siblings before being paired.…”
Section: Discussionmentioning
confidence: 59%
“…This effect is likely to be due to two interacting factors: a decrease in the average litter size born (in contrast with Tardif et al [1986], who found an increase), and an increase in the number of infants surviving from each litter. The delayed improvement occurred despite the fact that all breeding females had had considerable experience with infant siblings before being paired.…”
Section: Discussionmentioning
confidence: 59%
“…Attempts to breed Callitrichidae in captivity have resulted in high fertilit accompanied by high infant mortality (&bourn et al, 1983;Kirkwood et al, 1983;Tardif et al, 1986). This suggests that along with selection for increased litter size, there is strong selection perinatall on offspring phenotype.…”
mentioning
confidence: 93%
“…There has been extensive study of the maternal characteristics that affect postnatal infant survival in callitrichid primates [Tardif et al, 1986;Pryce et al, 1988Pryce et al, , 1993Pryce et al, , 1995Baker & Woods, 1992;French et al, 1996]. Variables that might affect the likelihood of conception or successful gestation, and therefore the number of infants born, have received less attention, particularly in wild populations.…”
Section: Introductionmentioning
confidence: 99%